SOSIALISASI PROGRAM PEGUNGKAPAN SUKARELA (PPS) UU NO. 7 TAHUN 2021 - Dedy Triyono; Bintang Marsha Anggraeni (LPPM Universitas Islam Darul 'Ulum Lamongan, 2022)
Law Number 7 of 2021 concerning Harmonization of Tax Regulations (UU HPP) is a continuation of Law Number 11 of 2020 concerning Job Creation (UU Ciptaker) in terms of regulating provisions in the taxation sector. The HPP Law regulates several changes and the inclusion of new provisions including the Voluntary Disclosure Program (PPS). One of the main objectives of PPS is to increase taxpayer compliance. PPS is implemented based on the principles of simplicity, legal certainty and benefit. Community service activities with the aim of providing an understanding to the public about PPS and its scope. The material presented in this socialization includes Indonesia's macroeconomic conditions, the impact of the pandemic situation, and the link between PSS and tax compliance.